Enhancing the performance of aluminium by chromium oxide - Gautam M.; Gautam G.; Mohan A.; Mohan S. (My University, 2025)
The present study deals with the effect of chromium oxide (Cr2O3) addition in the commercially pure Al to observe its effect on mechanical performance. The Cr2O3 powder reacted with molten Al at the 850 °C temperature and formed hybrid composites with different reinforcement particles. The composites so produced were subjected to different studies such as x-ray diffraction (XRD), optical microscopy, electron-microscopy with energy-dispersive spectroscopy (EDS), tensile testing and hardness evaluation. Results of XRD and EDS indicated that the particles of Al7Cr and Al2O3 were formed by the chemical reaction between Cr2O3 and Al. The Al7Cr particles were present in polyhedron and faceted morphology in a size range of 15-55 μm, whereas, Al2O3 particles showed the polyhedron morphology in a size range of 3-17 nm. Optical microscopy showed that the grain size of Al was refined by the formation of Al7Cr and Al2O3 particles and it continuously decreased with the increase in amount of particles. Strength parameters and hardness were improved with formation of reinforcement particles. Maximum improvement in mechanical properties was obtained in the case of HAMC3 (Hybrid Aluminium Matrix Composite3) composite with approximately 13 wt% of Cr2O3. Strengthening mechanisms and fractography were also studied and correlated with the microstructure and mechanical properties of the composites. © 2019 IOP Publishing Ltd.